RETRACTED: Experimental testing of the effectiveness of the Turan struggle in higher education - Arslonov Qaxramon; Ibragimov Mironshox; Koraboev Fazliddin; Abitova Jasmin (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001